HUBUNGAN ANTARA POLA ASUH ORANG TUA DENGAN KECENDERUNGAN LOCUS OF CONTROL REMAJA SLTP NEGERI 8 MALALAYANG - Beruat, Ruth G. R.; Opod, Hendry; Sinolungan, Jehosua V. (Universitas Sam Ratulangi, 2015)
Abstract: This study aimed to determine a possible link between parenting parents with a predisposition locus of control teens SLTP 8 Manado. The purpose of this paper is to obtain information through empirical data, the relationship of each parenting parents (permissive, authoritharian, authoritative, neglectful) with locus of control teens and get an idea of the locus of control teens SLTP 8 Manado and get an overview of locus of control SLTP 8 Manado. Locus of control is a belief in everyday life. Locus of control one often seen on the way we discript sense of causality that is relatively consistent. Various studies have shown that those who have a tendency internal locus of control are more successful pay attention, more selective towards stimulus, as well as more selective about the task, rather than those who tend to be external, individuals with a tendency external locus of control tend to have confidence. Thus the tendency of individuals with an internal locus of control more have more positive aspects in comparison with the external.Keywords: parents, teenagers, locus of controlAbstrak: Studi ini bertujuan untuk mengetahui kemungkinan adanya hubungan antara pola asuh orang tua dengan kecenderungan locus of control remaja SLTP Negeri 8 Manado. Adapun tujuan dari skripsi ini adalah memperoleh informasi melalui data empirik, mengenai hubungan masing-masing pola asuh orang tua (permissive, authoritharian, authoritative, neglectful) dengan locus of control remaja dan mendapatkan gambaran tentang locus of control remaja SLTP Negeri 8 Manado dan mendapatkan gambaran tentang locus of control SLTP Negeri 8 Manado. Locus of control merupakan keyakinan dalam hidupnya sehari-hari. Locus of control seseorang kerap terlihat dari caranya mengekspersikan sense of causality yang relative konsisten. Berbagai penelitian membuktikan bahwa mereka yang memiliki kecenderungan locus of control internal lebih berhasil mengarahklan perhatiannya,lebih selektif terhadap stimukus, serta lebih selektif terhadap tugas, daripada mereka yang cenderung eksternal, individu-individu dengan kecenderungan locus of control eksternal cenderung memiliki rasa percaya diri. Dengan demikian individu-individu dengan kecenderungan locus of control internal lebih banyak memiliki aspek yang lebih positif di bandingkan dengan eksternal.Kata kunci: orang tua, remaja, locus of control